Analisis Pengaruh Kualitas Laporan Keuangan, Kualitas Pelayanan Publik dan Transparansi Pengelolaan Keuangan terhadap Elektabilitas Kepala Daerah Incumbent di Indonesia - Fitrah Azirial Akbar; Amy Fontanella; Josephine Sudiman (Ekonomis: Journal of Economics and Business, 2026)
This study aims to examine the effect of financial report quality, public service quality, and financial management transparency on the electability of incumbent regional heads in Indonesia, with economic growth as a control variable. The research employs a quantitative approach using secondary data from 324 regencies/cities that participated in the 2024 regional elections. Data were analyzed using multiple linear regression with STATA version 17. The results show that public service quality has a positive and significant effect on the electability of incumbent regional heads, while financial report quality and financial management transparency have no significant effect. Simultaneously, all independent variables and the control variable significantly affect electability, although the model’s explanatory power remains low (Adjusted R² = 3.73%). These findings highlight that public service quality is the most relevant factor influencing public support for incumbents. The results are expected to provide insights for local governments and regional head candidates in formulating strategies to enhance electability through improved public service quality.